Legal Standing Pemohon dalam Pengajuan Uji Materiil Ditinjau Berdasarkan Teori Keadilan - Egidia Renanda Pradini; Qinthara Qamarani Haryanto; Dahayu Noer Asmara Putri; Aulia Fatimah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This research examines the legal standing of the Petitioner, Gerakan Satu Visi, in filing a judicial review of the Copyright Law (UUHC) based on Thomas Hobbes’ Theory of Justice and its legal implications. Using a normative juridical method with statutory and conceptual approaches, the study finds that the Petitioner does not meet the legal standing requirements under Article 51 of the Constitutional Court Law, as it failed to show direct, actual, and causal constitutional harm. The alleged financial loss is indirect, and the Petitioner’s related-rights status is derivative. As a result, the UUHC remains in force, royalty obligations and LMKN’s role are strengthened, and disputes shift to commercial civil proceedings.